Bowed Generation and Digital Ethics Challenges in Islamic Education - Yanti Yanti; Yulianto Nur Cahyono; Aida Hayani (West Science Islamic Studies, 2023)
Generation Bowing Down and the Challenges of Digital Ethics in Islamic Education" is a study that explores the impact of the evolution of digital technology on Islamic values among the younger generation. In an era where technologies like smartphones, the internet, and social media have become inseparable from daily life, the younger generation often finds themselves trapped in the "bowing down" behavior, directing their attention to gadget screens. In relation to Islamic education, this tendency presents significant ethical challenges. This research examines the effects of changing communication behaviors, learning patterns, and digital ethics in the digital era on Islamic educational practices. The focus is on how to teach Islamic values to the younger generation increasingly exposed to digital technology and how to address potential negative impacts that may arise. By delving deeper into the "generation bowing down" phenomenon and evaluating the aspects of digital ethics in education, this study also formulates an effective role for Islamic education in preserving fundamental Islamic values in the digital era. Through a deeper understanding of these dynamics, it can be an effort to prepare the younger generation to integrate digital technology into their lives in harmony with crucial Islamic values